Stimulasi Bahasa Anak Usia Dini Melalui Kegiatan Bernyanyi dan Bercerita - Amanda Maharani; Siti Alhayu Humaira; Nadia Azzahra; Meli Masita; Sipriani Sipriani; Riza Azka Fazila Azka Fazila; Silvia Anggraini (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
Singing, storytelling, and early childhood language development. Out of 2,500 identified articles, ten met the inclusion criteria and served as the primary sources for this review. Data were analyzed using a thematic analysis approach, involving the identification, categorization, and interpretation of findings based on relevant themes. The results indicate that the singing method is effective in enhancing vocabulary, pronunciation, memory, and children's participation in learning. The storytelling method is proven to improve listening and speaking skills, language comprehension, and children's confidence in communication. These findings demonstrate that both methods contribute positively to early childhood language development and can serve as alternative instructional strategies to support optimal language stimulation.